A coleção Matemática, metodologia e complementos para professores primários, de Ruy Madsen Barbosa: um estudo - Milanez, Natalia Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Essa pesquisa tem como objetivo analisar a coleção Matemática, metodologia e complementos para professores primários, utilizando o referencial teórico metodológico da Hermenêutica de Profundidade proposta por Thompson, em conjunto com a ideia de Paratextos Editoriais, de Genette. A coleção é composta por 3 volumes, e foi escrita por Ruy Madsen Barbosa na década de 1960, uma das pouquíssimas obras desse autor voltada para o ensino primário. A análise é constituída de comentários sobre a obra, sua circulação, seu contexto e seu autor, criando como que um cenário para essa produção didática, apontando tanto elementos que, nela, nos pareceram inovadores do ponto de vista didático e pedagógico, quanto o modo como, nela, aparentemente, seu autor defende valores próprios à prática científica da Matemática.

This text has as its main goal to perform an hermeneutic exam of a set of books entitled Mathematics, Methodology and Complements for elementary school teachers. Such analysis was developed according to Thompson´s Hermeneutics of the Deph and the idea of paratexts as proposed by Genette. The set has three volumes and was published in 1960´s by Ruy Madsen Barbosa. It was one among the few textbooks of this author dedicated to elementar schools. Such hermeneutic exam is composed putting together some remarks on the content and treatment, in the texts, to the mathematical concepts and heuristics, the producing process and circulation of the books, their context and author, focusing some points that can be considered innovations from a didactical and pedagogical point of view, but also elements more conservatives more conservatives, like those in which author seems to defend some values related to the scientific practice of professional Mathematics.
The set of books Mathematics, Methodology and Complements for elementary school teachers, by Ruy Madsen Barbosa: one study
Keywords: Hermenêutica de profundidade; História da educação matemática brasileira; Década de 1960; Análise de livros; Movimento Matemática Moderna e o GEEM – Grupo de Estudos do Ensino da Matemática; Hermeneutics of the depth; History of mathematics education in Brazil; 1960´s; Textbook analysis; New Math Movement and GEEM – Math Teaching Study Group